1998
DOI: 10.1152/jappl.1998.85.5.1949
|View full text |Cite
|
Sign up to set email alerts
|

Force-velocity-power and force-pCa relationships of human soleus fibers after 17 days of bed rest

Abstract: Soleus muscle fibers from the rat display a reduction in peak power and Ca2+ sensitivity after hindlimb suspension. To examine human responses to non-weight bearing, we obtained soleus biopsies from eight adult men before and immediately after 17 days of bed rest (BR). Single chemically skinned fibers were mounted between a force transducer and a servo-controlled position motor and activated with maximal (isotonic properties) and/or submaximal (Ca2+ sensitivity) levels of free Ca2+. Gel electrophoresis indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
75
2
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(86 citation statements)
references
References 30 publications
8
75
2
1
Order By: Relevance
“…Widrick and coworkers (28) showed that in one subject out of eight, fiber diameter remained unchanged and P 0 was increased after 17 days of bedrest, whereas average values showed significant decreases in both variables. This individual also had increases in V 0 and fiber power (27,28). In another investigation from the same group, one out of four astronauts did not display a decrease in fiber diameter following a 17-day spaceflight mission, in contrast to the other three astronauts (26).…”
Section: Single Fiber Csa and Pmentioning
confidence: 78%
See 1 more Smart Citation
“…Widrick and coworkers (28) showed that in one subject out of eight, fiber diameter remained unchanged and P 0 was increased after 17 days of bedrest, whereas average values showed significant decreases in both variables. This individual also had increases in V 0 and fiber power (27,28). In another investigation from the same group, one out of four astronauts did not display a decrease in fiber diameter following a 17-day spaceflight mission, in contrast to the other three astronauts (26).…”
Section: Single Fiber Csa and Pmentioning
confidence: 78%
“…Experiments based on single fiber models have demonstrated great sensitivity in detecting also a certain degree of functional variability of fibers expressing the same MHC isoforms, especially when the pattern of muscle activity changes. Human studies involving 17 days of bed rest (27,28) or spaceflight (26) revealed that maximal single fiber force (P 0 ) from the soleus muscle was decreased, mainly as a result of a decline in fiber cross-sectional area (CSA), and that maximal unloaded shortening velocity (V 0 ) was increased. Consequently, single fiber power was either maintained or depressed, depending on the study participant or fiber type (29), with fibers expressing type I MHC being generally more affected.…”
mentioning
confidence: 99%
“…The single fiber isolation and test procedures were exactly as described previously (21,22) and briefly reviewed here. On the day of Values are means Ϯ SE.…”
Section: Subjectsmentioning
confidence: 99%
“…Fibers were subjected to slack tests to measure unloaded maximal shortening velocity (V 0), and the force-velocity relation was determined from a series of isotonic releases as described previously (21). P 0 was defined as the peak force obtained during the experiment.…”
Section: Subjectsmentioning
confidence: 99%
See 1 more Smart Citation